Student-centered research : blending constructivism with action research - Pelech, James (Emerald Publishing Limited : Information Age Publishing Inc., 2021)
"Teachers increasingly are being charged to conduct research on teaching and learning in their classes. Action research is an instrument that teachers can use for their particular classroom to meet this charge. While traditional research provides effective guidelines for teaching and learning, its generalized format does not take into consideration the multitude of variables that affect individual classrooms and students. Action research enables the teacher to improve the learning of the students in their particular context; this, in turn, improves the professional practice of the teacher. The uniqueness of the model presented in this book is that this model is guided by specific Constructivist principles. These principles are then transformed into learning strategies and applied to the action research cycle. Each stage of the action research process also is steered by prompts emanating from the Constructivist philosophy. The prompts provide questions that the teacher can use to examine current practices and consider new approaches. The blending of Constructivism and action research enables the teacher to create a new cognitive framework for understanding and enhancing student learning . This book provides a guide for combining two important traditions resulting in a research platform which creates new knowledge about both students and teachers"-- Provided by publisher.
Keywords: Action research in education.; Constructivism (Education); Student-centered learning.; Education -- Research.; Philosophy and theory of education.; Education.; elektronické knihy; electronic books